Model of Prevention of Vaginal Discharge in Adolescents Based on Determinants of Health Literacy - Warini, Warini; Nura Suciati Fauzia; Istiqomatunnisa, Istiqomatunnisa (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The impact of vaginal discharge is very fatal if it is slow to be treated, not only can it lead to infertility and pregnancy outside the womb due to blockage of the fallopian tubes, vaginal discharge can also be an early symptom of uterine cancer which can lead to death. The purpose of the study was to produce a model and determine the most influential factors on health literacy in preventing vaginal discharge in adolescents. This type of research is quantitative with a cross sectional research design. The population of this study were all adolescents in Puspasari Village, Bogor Regency. The research sample amounted to 90 people. Determination of sample size using purposive sampling. Research data collection using a questionnaire. The results showed that there was an influence of health promotion by 21.42%, the role of midwives by 22.66%, family function by 16.88%, social environment by 11.04% and self efficacy by 9.65% on health literacy in preventing vaginal discharge in adolescents. Based on the R-Square value, the direct effect of health promotion, the role of midwives, family function, social environment and self efficacy on health literacy in preventing vaginal discharge in adolescents is 81.65% while 18.35% is explained by other variables not studied. It is hoped that the role of health workers in providing counseling related to the prevention of vaginal discharge, such as making breakthroughs for the renewal of vaginal discharge prevention.